Antibiotics Treatment for Acute Respiratory Tract Infections (ARTIs): Evaluation of Doxycycline Resistance Cases at a Community Health Center in Urban Area of Indonesia. - Danni - Ramdhani (Journal of Global Pharma Technology, 2020)
Abstract. Acute respiratory tract infections (ARTIs) are a major health problem in developing countries. This infection can occur in the upper or lower respiratory tract which is accompanied by inflammation. Doxycycline is highly recommended for the treatment of ARTIs patients allergic to penicillin. This study aimed to evaluate the effectiveness of doxycycline in the treatment of ARTIs through its antibiotic resistance rates, and identify bacteria that have been resistant to doxycycline antibiotics. This study consists of the stages of rejuvenation of clinical isolates from ARTIs patients at a community health center in the Urban Tasikmalaya area, identification of bacteria, and testing for antibiotic resistance using the paper-disk method. The results of resistance tests from 116 single clinical isolates showed that there had been resistance to doxycycline antibiotics in the treatment of ARTIs in the urban area of Tasikmalaya with a category of 64.29% being resistant; 14.29% intermediates and 21.42% are still sensitive. The results of bacterial identification showed that doxycycline was resistant to the Corynebacterium, Streptococcus, Staphylococcus, Haemophillus and Bordetella bacteria groups. Doxycycline treatment for ARTIs infection is considered not very effective. Another class of drugs as a substitute for doxycycline for patients allergic to penicillin is needed.